Smart(phone) travelling: understanding the use and impact of mobile technology on irregular migration journeys. (2017) - Zijlstra, Judith; Liempt, Ilse Van
This article analyses how mobile technology impacts on irregular migrants' journeys. It is based on trajectory ethnography with 11 Afghan, Iranian and Syrian migrants whom the first author met in Turkey and Greece in the spring of 2015. These migrants were followed (partly digitally) to Serbia, Hungary, Germany, Sweden and the Netherlands. We argue that the method of trajectory ethnography is a useful tool that allows us to understand how mobile technology shapes and facilitate parts of the journey - like, for example, decisions on routes and modes of travel, final destinations and the financing of irregular migration. This methodology leads to a more nuanced understanding of irregular migration because it enables us to capture the complex dynamics involved in irregular migration processes and to reflect on decisions taken within the process.